1998
DOI: 10.1046/j.1365-3156.1998.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole plus praziquantel versus albendazole alone as a pre‐operative treatment in intra‐abdominal hydatidosis caused by Echinococcus granulosus

Abstract: Albendazole plus praziquantel is more effective than monotherapy with albendazole in the preoperative treatment of intra-abdominal hydatidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 16 publications
0
121
0
3
Order By: Relevance
“…[19][20][21][22] Over the past few decades, other anthelmintic chemotherapies such as praziquantel and nitazoxanide have also been tested against Echinococcus spp., but their efficacies are inferior to those of benzimidazoles. 16,23,24 Despite this, the combination of albendazole with praziquantel has shown synergistic activity against Echinococcus spp. In fact, observational studies suggest that the combined therapy could improve the cure rates obtained with albendazole alone [23][24][25][26] ; regarding the safety of medical therapy, an increase in transaminases levels is the most frequent adverse reaction related to albendazole treatment, 27 whereas digestive symptoms are the most frequent adverse effects associated with praziquantel in monotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] Over the past few decades, other anthelmintic chemotherapies such as praziquantel and nitazoxanide have also been tested against Echinococcus spp., but their efficacies are inferior to those of benzimidazoles. 16,23,24 Despite this, the combination of albendazole with praziquantel has shown synergistic activity against Echinococcus spp. In fact, observational studies suggest that the combined therapy could improve the cure rates obtained with albendazole alone [23][24][25][26] ; regarding the safety of medical therapy, an increase in transaminases levels is the most frequent adverse reaction related to albendazole treatment, 27 whereas digestive symptoms are the most frequent adverse effects associated with praziquantel in monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…16,23,24 Despite this, the combination of albendazole with praziquantel has shown synergistic activity against Echinococcus spp. In fact, observational studies suggest that the combined therapy could improve the cure rates obtained with albendazole alone [23][24][25][26] ; regarding the safety of medical therapy, an increase in transaminases levels is the most frequent adverse reaction related to albendazole treatment, 27 whereas digestive symptoms are the most frequent adverse effects associated with praziquantel in monotherapy. Anaphylactic reactions related to praziquantel have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the bioactive fraction in our crude extract might have some compound that has activity like pyrazinoisoquinoline derivative and selectively active on tegumental surface. In few of the recent studies, it was observed that praziquantel have substantial effect when used in combination of other scolicidal agents such as albendazole (Cobo et al 1998). Therefore, we speculate that our extract together with other synthetic drug/s might be more effective.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover Albendazole at daily 40 mg/kg dose combined with another chemotherapeutic praziquantel for 1 week has been shown to be more effective than Albendazole alone [28].…”
Section: Treatmentmentioning
confidence: 99%